2017
DOI: 10.1016/j.jand.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sugar-Sweetened Beverage Consumption among Low-Income Children: Are There Differences by Race/Ethnicity, Age, and Sex?

Abstract: Background Understanding determinants of high consumption of sugar-sweetened beverages (SSB), a highly prevalent obesogenic behavior, will help build effective customized public health interventions. Objective To identify child and parent lifestyle and household demographic factors predictive of high SSB consumption frequency in children from low-income, ethnically diverse communities that may help inform public health interventions. Design Cross-sectional telephone household survey. Participants/Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 24 publications
4
62
1
1
Order By: Relevance
“…Han and Powell reported similar, but less robust results in their study on the association between lower levels of education and consumption of total SSBs ( OR = 1.34, 95% CI = 1.23, 1.47) or sodas only ( OR = 1.52, 95% CI = 1.39, 1.67) ( 21 ), as did Qobadi and Payton, in their study of SSB consumption in Mississippi ( OR = 1.9, 95% CI = 1.4, 2.6) ( 23 ). Two additional studies revealed an association between choosing SSBs for children and lower levels of education ( 30 , 31 ). Most striking in our study was the association between education and consumption of three or more SSBs per day.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Han and Powell reported similar, but less robust results in their study on the association between lower levels of education and consumption of total SSBs ( OR = 1.34, 95% CI = 1.23, 1.47) or sodas only ( OR = 1.52, 95% CI = 1.39, 1.67) ( 21 ), as did Qobadi and Payton, in their study of SSB consumption in Mississippi ( OR = 1.9, 95% CI = 1.4, 2.6) ( 23 ). Two additional studies revealed an association between choosing SSBs for children and lower levels of education ( 30 , 31 ). Most striking in our study was the association between education and consumption of three or more SSBs per day.…”
Section: Discussionmentioning
confidence: 98%
“…Perceived less healthy diet and drinking <8 cups of water per day were also consistently associated with SSB in our study. Tasevska and associates also reported an association between consumption of SSB and eating a healthy diet (measured by eating breakfast 6 or 7 days per week) ( 30 ). Although Qobadi and Payton reported an association between consumption of SSBs and eating in fast-food restaurants, our study did not uncover a similar association ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the current study includes younger children, for whom self-reports are not a viable instrument, parent reports of consumption were used for children of all ages (3-18 years old). This approach was used to ensure consistency of responses across age groups and households and is in line with previous research [20,21].…”
Section: Analytical Variablesmentioning
confidence: 92%
“…The soft drink industry argues that sugar taxes disproportionately and unfairly affect those from lower socio‐economic households. These groups spend more of their income on high sugar products than other households . Evidence from Berkeley California suggests that substantial sugar taxes do not necessarily make poorer communities worse off.…”
Section: Political Barriers To a Sugar Tax Implementationmentioning
confidence: 99%